UPTAKE AND UTILISATION OF NATIONAL GUIDELINES FOR TUBERCULOSIS INFECTION, PREVENTION AND CONTROL AMONG NURSES WORKING IN RESOURCE-LIMITED SETTINGS; A CROSS-SECTIONAL STUDY IN UGANDA. - Byanga, Ivan; Kabwigu, Samuel (Student’s Journal of Health Research Africa, 2024)
Background This study assessed the uptake and utilization of the “Uganda National Guidelines for TB IPC” among nurses working within health facilities in Bundibugyo District, Western Uganda. With a focus on knowledge, practices, and perceived barriers, based on a customized health belief model. Methods Focused on nurses, the research employed a cross-sectional design using qualitative and quantitative methods with a census technique involving 135 participants across 11 healthcare institutions, that manage TB cases within Bundibugyo district. Quantitative data was captured utilizing self-administered questionnaires and qualitative data by 11 KI and observational checklists, analyzed, and then presented in tables and narrations. Key findings The majority were enrolled nurses (42.9%), and gaps in nurses’ recognition of the TB guidelines were attributed to limited training sessions. While nurses exhibited high knowledge of basic TB aspects, their awareness of the policy of handling TB clients in their facilities was low at 47.4% and only 35.5% of them had participated in a TB-related training or workshop during the past 2 years, weaknesses were further noted in the screening of patient beds, patient isolation units, and nose-covering practices. Perceived barriers included TB stigma, false beliefs, infrastructure inadequacies, and resources like PPE shortages. Conclusion There was insufficient uptake and utilization of the Guidelines within medical facilities in Bundibugyo. This is linked to a few trainings and acquaintance of the guidelines among nurses which have created knowledge gaps and other barriers: resources, stigma, and false beliefs within the surrounding communities. Recommendations Enhancing training programs, promoting awareness within health facilities, improving infrastructure, implementing monitoring and evaluation systems, allocating more resources, and addressing weaknesses in implementation. MoH Uganda; Policy review, centralize training programs, and continue research and development. Further research recommendations encompass in-depth studies on TB stigma, evaluating training impacts, and conducting longitudinal studies.